The effects of different BAP concentrations on axillary budding and branching of Orthosiphon stamineus plant - Mohd Sinin, Siti Sarah (2016)
Orthosiphon stamineus or commonly known as “misai kucing” in Malaysia is one of the medicinal herb from Lamiaceae family that originates from Southeast Asia. It has several important uses in terms of medicinal and economic value and as ornamental plant. Orthosiphon stamineus is currently propagated by stem cuttings for production of planting materials. However, propagation through stem cutting resulted in inadequate supply of planting materials for large market demand. In order to solve this problem, application of BAP (6-Benzylaminopurine) could trigger axillary branching and thus produce large quantity of stem cutting for production of planting materials. A study was conducted by using different concentration of BAP to trigger axillary branching of Orthosiphon stamineus plant. This experiment was carried out at the Tissue Culture Laboratory, Department of Agriculture Technology, Faculty of Agriculture, Universiti Putra Malaysia. There were five treatments of BAP at different concentrations which are 0, 25, 50, 75, and 100 mg/L with six replications for each treatment. The experiment was conducted using randomized complete block design (RCBD). Analysis of data is carried out using ANOVA and treatments mean was tested using DMRT test. The plants growth was monitored for 4 weeks. Number of days taken for bud proliferation, number of axillary shoots proliferation and the length of branching was recorded. A 50mg/L BAP concentration sprayed on nodes of Orthosiphon stamineus plant is better treatment since the plant produced high axillary proliferation (14.5). However, the application of BAP at different concentration on the nodes of the plant reduced its branching length.